Automação como suporte ao manejo sustentado da irrigação na cultura da alface no no município de Itabaiana - SE - Giacomelli, Waldiney (2011)
The present work was developed in the experimental area of the project "Pequeno Produtor, Grande Empreendedor that it is an area of vegetables production. It is located in the municipal district of Itabaiana in the state of Sergipe. The objective was to project and to create an automatized control of an irrigation system by leak, verifying the productive aspects related to the sustainability indicators. The calculation for water replacement in the soil was based on the estimate of the evapotranspiration starting from the reading of the climatological greatness accomplished by the agriculture-meteorological station installed at the experiment place. The equation of Penman-Montheith was used, recommended by the Food and Agricultural Organization of the United Nations (FAO). Once the estimated evapotranspiration was known, the control system did the other calculations to establish the time for the replacement of the necessary water sheet. The final comparison between the experiment and the normal production used by the producer points to a significant profit in the consumption of water and electric power. The microcontrolled control besides contributing for the decrease of the consumption of water supplies and electric power also provided an economy in the maintenance of the installed equipments. Doing so, a possibility of a higher economical profit is presented, contributing for life improvement of the small family producers, making their social and economic indicators better.